Policy innovation lab scholarship: past, present, and the future – Introduction to the special issue on policy innovation labs. Issue 2 (3rd April 2021) - Wellstead, Adam M.; Gofen, Anat; Carter, Angie
Abstract: The past decade has seen a rapid rise in the number of policy innovation labs (PILs). PILs that are found both inside and outside of government address a wide range of social issues. Many PILs share a few distinct common characteristics: a commitment to the design-thinking methodology, a focus on applying experimental approaches to testing and measuring the efficacy of comprehensive public policy and intervention program prototypes, and the use of user-centric techniques to stakeholders in the design process. In this introduction to the special issue on PILs, we begin by taking stock of the policy lab literature published to date by providing an overview of 70 related publications (peer review articles, book chapters, theses, reports, and catalogs) and the extent that they engage the policy literature. This review demonstrates the underexplored practitioner perspective, which serves as the theme for this special issue. Next, the six articles that comprise this special issue are introduced. They are written from a practitioner perspective and include contributions from Brazil, Canada, Finland, and the United Kingdom. Finally, suggestions for future research are highlighted, including the role of PILs in policy work, PILs as street-level policy entrepreneurship settings, and the need for more rigorous inferential methods.